Etika dalam Asesmen Psikologi di Bidang Bimbingan dan Konseling - Eva Apriyani Mahmud (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to comprehensively examine ethics in psychological assessment withim the field of guidance and counselling. Ethics in psyshological evaluation serve as a fundamental basis to ensure services are professional, respectful and compliant with prevailing legal standards. Ethical principles such as confidentiality, objectivity, fairness, and competence are essential foundations that help clients feel comfortable and conflident in expressing their problems. Counsellor and psychologists are required to maintain the confidentiality of assessment results and avoid conflicts of interest in their duties. However, the implementation of ethical codes in psyschologis assessment still faces various challenges, including lack of understanding, limited training, and knowledge about ethics is crucial so that counsellors and psyshologists can provide superior and high-integrity psyshological assessment services. Ethics in psychological assessment not only serve to protect clients’ rights but also uphold the profession’s reputation and improve the overall quality of guidance and counselig services.